2017
DOI: 10.1158/1940-6207.capr-17-0141
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of a Genetic Risk Score into a Validated Risk Prediction Model for Colorectal Cancer in Japanese Men Improves Performance

Abstract: We previously developed and validated a risk prediction model for colorectal cancer in Japanese men using modifiable risk factors. To further improve risk prediction, we evaluated the degree of improvement obtained by adding a genetic risk score (GRS) using genome-wide association study (GWAS)-identified risk variants to our validated model. We examined the association between 36 risk variants identified by GWAS and colorectal cancer risk using a weighted Cox proportional hazards model in a nested case-control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…[18][19][20][21] Recent studies have demonstrated that combination of environmental and genetic factors may substantially improve prediction of CRC risk. [22][23][24][25] However, to the best of our knowledge, no previous study has combined information from environmental risk scores (ERS) and genetic risk scores (GRS) for predicting the presence of CRC and its precursors, the targets for CRC screening, in a true screening setting.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Recent studies have demonstrated that combination of environmental and genetic factors may substantially improve prediction of CRC risk. [22][23][24][25] However, to the best of our knowledge, no previous study has combined information from environmental risk scores (ERS) and genetic risk scores (GRS) for predicting the presence of CRC and its precursors, the targets for CRC screening, in a true screening setting.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of new cases and deaths occur in people of age 50 and older 1 . About 35% of the susceptibility to CRC is attributed to genetic factors, while the remaining 65% is attributed to non-modifiable and modifiable environmental factors such as age (particularly, 40 to 69 years), obesity, high fat diet, smoking, alcohol, and Type II diabetes (T2DM) [2][3][4][5] . The effect of the obesity-related lifestyle factors on CRC risk may be mediated by insulin-like growth factor-I (IGF-I)/insulin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, lifestyle and life-environment factors among the Japanese population have undergone drastic changes during these decades, 3 and many molecular epidemiological studies have reported associations between genetic and environmental factors and diseases [4][5][6] and identified biomarkers that may be useful in predicting disease risk in individuals. 7,8 The addition of such biomarker information to environmental factors will be helpful in establishing personalized healthcare.…”
Section: Introductionmentioning
confidence: 99%